APLIKASI SISTEM CERDAS SEBAGAI PENENTU KEBIJAKAN MANAJEMEN RESIKO SISTEM KETENAGALISTRIKAN - Kaloko, Bambang Sri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
An electricity based on artificial intelligence has been developed for producing a cheap, simple, and reliable electricity method. The comparison of reability value and availability value of old method that applied now in Buduran Substation with a new expert system method has been tested. The evaluation of change of reability value and availability value of a new expert system method showed a value <10%. It is concluded that this method is acceptable. The decreasing of reability value and availability value of new method can be used for the maintening of equipment.